Overexpression of Glutathione S-Transferases in Human Diseases: Drug Targets and Therapeutic Implications - Ning Lv; Chunyan Huang; Haoyan Huang; Zhiqiang Dong; Xijing Chen; Chengcan Lu; Yongjie Zhang (MDPI AG, 2023)
Glutathione S-transferases (GSTs) are a major class of phase II metabolic enzymes. Besides their essential role in detoxification, GSTs also exert diverse biological activities in the occurrence and development of various diseases. In the past few decades, much research interest has been paid to exploring the mechanisms of GST overexpression in tumor drug resistance. Correspondingly, many GST inhibitors have been developed and applied, solely or in combination with chemotherapeutic drugs, for the treatment of multi-drug resistant tumors. Moreover, novel roles of GSTs in other diseases, such as pulmonary fibrosis and neurodegenerative diseases, have been recognized in recent years, although the exact regulatory mechanisms remain to be elucidated. This review, firstly summarizes the roles of GSTs and their overexpression in the above-mentioned diseases with emphasis on the modulation of cell signaling pathways and protein functions. Secondly, specific GST inhibitors currently in pre-clinical development and in clinical stages are inventoried. Lastly, applications of GST inhibitors in targeting cell signaling pathways and intracellular biological processes are discussed, and the potential for disease treatment is prospected. Taken together, this review is expected to provide new insights into the interconnection between GST overexpression and human diseases, which may assist future drug discovery targeting GSTs.